Structural Breaks dan Ketidakstabilan Permintaan Uang di Indonesia - Deviyantini, Deviyantini; Sugema, Iman; Irawan, Tony (Jurnal Ekonomi dan Pembangunan Indonesia, 2017)
This research aims to identify the sources of instability of the money demand function (M1 and M2) due to structural changes that occur as a result of economic shocks. These shocks, are technically shown by the presence of structural breaks in the data and can lead the parameters non-constancy. The instability of the money demand function was analyzed using the Gregory and Hansen test. The source of instability of the money demand was identified using time varying parameter model. This research used quarterly time series data from 1993Q1 to 2013Q4. The result of Gregory and Hansen test indicates there is no long term equilibrium between variables (money demand, income, domestic interest rate, foreign interest rate, exchange rate, and inflation) in the model, neither M1 nor M2 model. On the other word, money demand function is unstable. The source of the instability is exchange rate variable.